Kesetaraaan Gender dan Implikasinya Terhadap Perilaku Sosial dalam Perspektif Sila Kelima Pancasila - Setiyowati, Eka Yuli (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2024)
This article discusses gender equality and its implications for social behavior in the perspective of the fifth principle of Pancasila. Using a literature-based qualitative research method, this article examines three main aspects, namely the condition of gender equality in Indonesia, the relationship between gender equality and the values of the fifth principle of Pancasila, and its impact on social behavior. Gender equality includes equal rights and opportunities for women and men in various fields, including education, employment and decision-making. Although the government has made steps to support gender equality, there are still inequalities that need to be addressed. This article aims to provide a deeper understanding of the importance of gender equality in building a just and civilized society in accordance with the values of Pancasila, especially the fifth principle.